2006
DOI: 10.1002/mnfr.200500219
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a new dechlorinated ochratoxin A derivative formed in opossum kidney cell cultures after pretreatment by modulators of glutathione pathways: Correlation with DNA‐adduct formation

Abstract: Ochratoxin A (OTA), a nephrotoxic mycotoxin probably implicated in human Balkan endemic nephropathy and associated urothelial tumors, induces renal carcinomas in rodents and nephrotoxicity in pigs. OTA induces DNA-adduct formation, but the structure of the adducts and their role in nephrotoxicity and carcinogenicity have only partly been elucidated. In vivo, 2-mercaptoethane sulfonate (MESNA) protects rats against OTA-induced nephrotoxicity but not against carcinogenicity, indicating two different mechanisms l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 53 publications
2
52
1
1
Order By: Relevance
“…To test the potential for conjugate formation by OTA, Dark Agouti rat liver and kidney samples were analysed for levels of OTA, OTα, OTB-GSH, OTHQ-GSH, OTB-NAC, and OTHQ-NAC, using HPLC with fl uorescence detection (34,35). The rat organ samples were available from a study in which 7-week-old Dark Agouti male and female rats were fed various concentrations of OTA in wheat for a period of 28 days; similar to the protocol previously reported (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the potential for conjugate formation by OTA, Dark Agouti rat liver and kidney samples were analysed for levels of OTA, OTα, OTB-GSH, OTHQ-GSH, OTB-NAC, and OTHQ-NAC, using HPLC with fl uorescence detection (34,35). The rat organ samples were available from a study in which 7-week-old Dark Agouti male and female rats were fed various concentrations of OTA in wheat for a period of 28 days; similar to the protocol previously reported (27).…”
Section: Discussionmentioning
confidence: 99%
“…The limit of detection (LOD) was 0.05 ng g -1 ; the limit of quantifi cation (LOQ) was 0.2 ng g -1 (34). The OTA metabolites were separated using a Prontosil C18 column (250 mm x 4 mm, particle size 3 μm) with solvent A: methanol:acetonitrile:6.5 mmol L -1 ammonium formate (200:200:600) adjusted to pH 3 with formic acid; and solvent B: methanol: acetonitrile:6.5 mmol L -1 ammonium formate (350:350:300) adjusted to pH 3 with formic acid, using gradient elution, as outlined previously (34,35). Detection was also performed using the fl uorimeter GTI spectrovision (λ ext =340 nm; λ em =465 nm) that permitted a LOD of ~ 0.05 ng g -1 for OTA.…”
Section: Ota and Ota Metabolite Analysismentioning
confidence: 99%
“…In this case the LOD for OTA-GSH showed a 3-fold increase using OTHQ parameters (trace (1)) compared to the LOD using parameters for OTA detection (trace (2)). This increased sensitivity may facilitate the detection of OTA metabolites bearing a C5-OH group [28,30,38] in biological fluids and enhance our understanding of OTA-mediated toxicity.…”
Section: Lc/fld Of Othq and Ota-gshmentioning
confidence: 98%
“…(43). We have demonstrated that both oxidative stress and covalent binding are involved in OTA nephrotoxicity and carcinogenicity (90) while Faucet-Marquis et al (91) established a correlation between DNA adducts and OTA derivatives in an opossum kidney cell culture (91).When applied to renal tubular cells, OTA led to GSH depletion (92). Using primary human urothelial cells from several donors, Lebrun et al (93) pointed out the role of genetic GST expression and the extent of DNA damage induced by OTA.…”
Section: Figure 4 Blood (B) and Urine (C) Ota Derivatives In Men And mentioning
confidence: 98%